Lack of AKT in adipocytes causes severe lipodystrophy - Abigail L. Shearin; Bobby R. Monks; Patrick Seale; Morris J. Birnbaum (Elsevier, 2016)
Objective: Adipose depot mass is tightly regulated to maintain energy homeostasis. AKT is a critical kinase in the insulin-signaling cascade that is required for the process of adipogenesis in vitro. However, the role of AKT in the maintenance and/or function of mature adipocytes in vivo had not been examined. Methods: To study this, we deleted Akt1 and Akt2 in adipocytes of mice using the AdipoQ-Cre driver. Results: Strikingly, mice lacking adipocyte AKT were severely lipodystrophic, having dramatically reduced gonadal adipose and no discernible subcutaneous or brown adipose tissue. As a result, these mice developed severe insulin resistance accompanied by fatty liver, hepatomegaly and with enlarged islets of Langerhans. Conclusions: These data reveal the critical role of adipocyte AKT and insulin signaling for maintaining adipose tissue mass. Author Video: Author Video Watch what authors say about their articles Keywords: Akt, Lipodystrophy, Insulin signaling, Insulin resistance